Leisure participation among parents of children with special needs / Nur Atiqah Azman, Tahira Hamidun and Ahmad Zamir Che' Daud - Azman, Nur Atiqah; Hamidun, Tahira; Che' Daud, Ahmad Zamir (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Restrictions to engage in leisure participation were commonly cited in previous studies especially those with children with special needs (SNC). This study aimed to determine the level of leisure participation among parents with SNC and to examine the differences between the mothers' and fathers' leisure participation and whether there is an association between the level of leisure participation and the type of child's disability. Seventy-five participants completed a questionnaire with demographic information and the Modified Interest Checklist used to evaluate leisure participation in the past, present and future. Participants showed moderate level of leisure participation and the highest participation among the activities listed were in the activities of daily living (ADL) group. The differences among the activities participated between mothers and fathers were significant, with mothers showing highest participation in ADL. However, the level of leisure participation among the parents did not show any association with the types of child's disability that they reared. Professional healthcare should not only consider the intervention progress for the child, but also the parents' leisure participation in an effort to produce the best outcome for the child itself.